A new three‐dimensional magnetopause model with a support vector regression machine and a large database of multiple spacecraft observations. Issue 5 (23rd May 2013) - Wang, Y.; Sibeck, D. G.; Merka, J.; Boardsen, S. A.; Karimabadi, H.; Sipes, T. B.; Šafránková, J.; Jelínek, K.; Lin, R.
Abstract : [1] We present results from a new three‐dimensional empirical magnetopause model based on 15, 089 magnetopause crossings from 23 spacecraft. To construct the model, we introduce a Support Vector Regression Machine (SVRM) technique with a systematic approach that balances model smoothness with fitting accuracy to produce a model that reveals the manner in which the size and shape of the magnetopause depend upon various control parameters without any assumptions concerning the analytical shape of the magnetopause. The new model fits the data used in the modeling very accurately, and can guarantee a similar accuracy when predicting unseen observations within the applicable range of control parameters. We introduce a new error analysis technique based upon the SVRM that enables us to obtain model errors appropriate to different locations and control parameters. We find significant east‐west elongations in the magnetopause shape for many combinations of control parameters. Variations in the Earth's dipole tilt can cause significant magnetopause north/south asymmetries and deviation of the magnetopause nose from the Sun‐Earth line nonlinearly by as much as 5 Re. Subsolar magnetopause erosion effect under southward IMF is seen which is strongly affected by solar wind dynamic pressure. Further, we find significant shrinking of high‐latitude magnetopause with decreased magnetopause flaring angle during northward IMF. Key Points: A new 3D empirical magnetopause model that solves long lasting problems. Magnetopause east-west elongation and subsolar erosion under southward IMF Earth's dipole tile has a significant nonlinear effect on magnetopause shape.